Rosemary extract as a natural antioxidant in structured lipid systems: a sustainable approach to enhance stability of perilla seed oil based omega-3 fatty acid rich margarine - Dhiman, Aishwarya; Chopra, Rajni (Frontiers in Sustainable Food Systems, 2025)
IntroductionPolyunsaturated fatty acids (PUFAs) are highly susceptible to oxidative deterioration, limiting their application in functional food systems. Synthetic antioxidants such as TBHQ are widely used to delay lipid oxidation, but their long-term consumption raises health concerns. This study investigated the use of rosemary extract (RE) as a natural antioxidant to enhance oxidative stability of omega-3 fatty acid rich margarine developed with structured lipids derived from perilla seed oil (PeO).MethodsStructured lipid margarine (SLM) was developed using enzymatic interesterification of PeO, and RE was incorporated at concentrations of 500, 1000, 1500, and 2000 ppm. Samples were subjected to accelerated storage conditions using the Schaal oven test. Oxidative stability was evaluated by measuring peroxide value, acid value, p-Anisidine value, TOTOX index, conjugated dienes, conjugated trienes, and fatty acid composition. Antioxidant efficacy was compared with tert-butylhydroquinone (TBHQ, 200 ppm). Data were further analyzed by Principal Component Analysis (PCA).ResultsIncorporation of RE significantly delayed lipid oxidation in SLM, with reductions of about 40% in peroxide values compared to control samples at 1500 ppm. It reduced TOTOX index and the levels of conjugated dienes and trienes, indicating improved protection against primary and secondary oxidation. The p-Anisidine value showed reductions of 21.7%, 21.6%, 26.9%, 37.7%, and 29.3% for SLM and SLM with RE at 500, 1000, 1500, and 2000 ppm, respectively, compared to PeO. Antioxidant activity was concentration dependent, with 1500 ppm RE showing optimal stabilization. PCA confirmed that RE at 1500 ppm was comparable to TBHQ in enhancing stability.Discussion and conclusionThe study demonstrates effectiveness of RE as natural antioxidant capable of stabilizing PUFA rich structured lipids systems. At 1500 ppm, RE provided oxidative protection equivalent to TBHQ, with the upside of being sustainable, plant-derived alternative. The combined effect of enzymatic interesterification and natural antioxidant supplementation offers a dual strategy to improve the stability of functional fat based products, supporting RE as a promising substitute for synthetic preservatives in the food industry.